A benchtop capillary flow layer-by-layer (CF-LbL) platform for rapid assembly and screening of biodegradable nanolayered films. Issue 23 (27th October 2016) - Dong, Ziye; Tang, Ling; Ahrens, Caroline C.; Ding, Zhenya; Cao, Vi; Castleberry, Steven; Yan, Jiangtao; Li, Wei
Abstract : We report a benchtop platform to systematically study film thickness, surface roughness, biocompatibility and degradation of a series of biodegradable nanolayered films. Abstract : Capillary flow layer-by-layer (CF-LbL) is a microfluidic platform for high throughput preparation and screening of nanolayered polymer films. Using a simple benchtop version of CF-LbL, we systematically studied the effects of various flow conditions and channel geometries on the thickness and surface roughness of the resulting films. We also investigated the biocompatibility and degradation behaviors of a series of enzymatically-degradable films made from naturally derived polymers, i.e. either alginate or hyaluronic acid as the anionic species and poly-l -arginine as the positive species. Furthermore, using one optimized film formulation for coating on the inside walls of a microfluidic chip, we successfully demonstrated the ability of this film to capture and rapidly release cancer cells from whole blood. This simple platform is expected to be a powerful tool to increase the accessibility of the LbL film assembly to a broader scientific community.